A Kinase‐Independent Function of c‐Src Mediates p130Cas Phosphorylation at the Serine‐639 Site in Pressure Overloaded Myocardium. Issue 12 (8th October 2015) - Palanisamy, Arun P.; Suryakumar, Geetha; Panneerselvam, Kavin; Willey, Christopher D.; Kuppuswamy, Dhandapani
ABSTRACT Early work in pressure overloaded (PO) myocardium shows that integrins mediate focal adhesion complex formation by recruiting the adaptor protein p130Cas (Cas) and nonreceptor tyrosine kinase c‐Src. To explore c‐Src role in Cas‐associated changes during PO, we used a feline right ventricular in vivo PO model and a three‐dimensional (3D) collagen‐embedded adult cardiomyocyte in vitro model that utilizes a Gly‐Arg‐Gly‐Asp‐Ser (RGD) peptide for integrin stimulation. Cas showed slow electrophoretic mobility (band‐shifting), recruitment to the cytoskeleton, and tyrosine phosphorylation at 165, 249, and 410 sites in both 48 h PO myocardium and 1 h RGD‐stimulated cardiomyocytes. Adenoviral mediated expression of kinase inactive (negative) c‐Src mutant with intact scaffold domains (KN‐Src) in cardiomyocytes did not block the RGD stimulated changes in Cas. Furthermore, expression of KN‐Src or kinase active c‐Src mutant with intact scaffold function (A‐Src) in two‐dimensionally (2D) cultured cardiomyocytes was sufficient to cause Cas band‐shifting, although tyrosine phosphorylation required A‐Src. These data indicate that c‐Src's adaptor function, but not its kinase function, is required for a serine/threonine specific phosphorylation(s) responsible for Cas band‐shifting. To explore this possibility, Chinese hamster ovary cells that stably express Cas were infected with either β‐gal or KN‐Src adenoviruses and used for Cas immunoprecipitation combined with mass spectrometry analysis. In the KN‐Src expressing cells, Cas showed phosphorylation at the serine‐639 (human numbering) site. A polyclonal antibody raised against phospho‐serine‐639 detected Cas phosphorylation in 24–48 h PO myocardium. Our studies indicate that c‐Src's adaptor function mediates serine‐639 phosphorylation of Cas during integrin activation in PO myocardium. J. Cell. Biochem. 116: 2793–2803, 2015. © 2015 Wiley Periodicals, Inc.